Revolusi Mental dalam Perspektif Budaya Jawa: Analisis Melalui Pemikiran Pierre Bourdieu - Prayitno, Ujianto Singgih (Jurnal Aspirasi, 2017)
The socio-cultural conditions of today's society are increasingly worrisome, whether viewed from the relationships between individuals or groups that are not harmonious, also the tendency of people who use violence as a mechanism to solve the problems they faced. Such concerns need to be resolved immediately, and the Mental Revolution as an idea gains its momentum. The approach developed in this analysis is the concepts of practice and action implementation, by examining the role of Javanese culture. The selection of Javanese Culture as the basis for the development of Mental Revolution value is inseparable from the culture or ethnic Javanese as the largest ethnic group in Indonesia which reaches 40 percent of the population. Dominant culture is a substantive model that reflects the fact that there is a rule of action in social life that is mutually agreed upon in emerging social interactions. Most Javanese everywhere, tend to maintain their Javanese ethnicity in their daily lives.Kondisi sosial budaya masyarakat dewasa ini makin mengkhawatirkan, baik dilihat dari relasi antar individu ataupun kelompok yang tidak harmonis, juga kecenderungan masyarakat yang menggunakan kekerasan sebagai mekanisme penyelesaian masalah yang dihadapinya. Kekhawatiran tersebut perlu segera diselesaikan, dan revolusi mental sebagai sebuah gagasan mendapatkan momentumnya. Pendekatan yang dibangun dalam analisis ini adalah konsep-konsep praktik dan pelaksanaan tindakan, dengan mengkaji peran kebudayan Jawa. Pemilihan Budaya Jawa sebgai dasar bagi pengembangan nilai Revolusi Mental, tidak terlepas dari budaya atau etnik Jawa merupakan etnik terbesar di Indonesia yang mencapai 40 persen dari populasi. Kebudayaan dominan adalah sebuah model substantif yang merefleksikan kenyataan yang memperlihatkan adanya aturan main dalam kehidupan sosial yang disetujui bersama dalam interaksi sosial yang muncul. Kebanyakan orang Jawa dimanapun berada, cenderung untuk mempertahankan kesukubangsaan mereka yang Jawa dalam kehidupan sehari-hari mereka.